Religious Inclusivity Through Al-Islam And Kemuhammadiyahan Education: A Case From Universitas Muhammadiyah Palopo - Rizka; Suyadi, Suyadi (el-Tarbawi, 2025)
Although courses on multiculturalism and tolerance have emerged at state Islamic religious universities, to date, no state Islamic university has accepted non-Muslim students. In contrast, private Islamic religious universities, particularly Muhammadiyah universities, accept non-Muslim students. In fact, more than 60% of Muhammadiyah universities in eastern Indonesia have non-Muslim students. The urgency of this research is a critical analysis of Al-Islam and Kemuhammadiyahan (AIK) education for non-Muslims at UM Palopo. The purpose of this research is to discover the concept of multicultural AIK expressed by 20 non-Muslim students at UM Palopo in religion classes. This research uses a descriptive qualitative approach with non-Muslim students at UM Palopo as informants. The results show that the expression of multicultural religiosity among non-Muslim students at Muhammadiyah universities is very different from the multicultural concepts in studies of religious scriptures as they have developed so far. Non-Muslim students: Christians are becoming more Christian and Catholic students are becoming more devout in church, likewise Muslims are becoming more devout in worship. The findings of this study complement the theory of Christian Muhammadiyah (Krismuha) which has successfully managed multiculturalism in Papua.